Gone fishing: Adélie penguin site-specific foraging tactics and breeding performance - Olmastroni S.; Fattorini N.; Pezzo F.; Focardi S. (Antarctic Science, 2020)
The ecological drivers underlying breeding performance are expected to differ across the geographical range of seabird species, but few studies have compared trade-offs between colonies with different local conditions. During chick-rearing (2000–01), we compared the foraging trips, diet and breeding parameters of two Adélie penguin colonies in the Ross Sea, at Edmonson Point (EdPo; ~2000 breeding pairs) and Inexpressible Island (InIs; ~24 000 breeding pairs). Penguins from InIs travelled farther and performed longer feeding trips. The quantity of food brought to the nest was the same for the two colonies, but penguins from InIs brought more fish and less krill. Eggs hatched earlier at EdPo. Breeding success did not differ, but chick weight during hatching–fledging was greater at InIs. Despite worse weather conditions at InIs, the larger proportion of high-energy food brought by penguins from InIs (i.e. fish) may explain their offspring‘s better performance. In addition, the persistence of fast ice at EdPo may have led to greater energy expenditure of breeding individuals, possibly reducing chick growth. The greater intraspecific competition expected at InIs may have been reduced by longer foraging trips and/or counteracted by the more nutritious diet. Our findings reveal complex trade-offs between foraging effort and environmental constraints in determining the breeding performance of Adélie penguins.